2020
DOI: 10.1111/febs.15665
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 integrates matrix mechanosensing with Ca2+ signaling to regulate extracellular matrix remodeling

Abstract: In healthy connective tissues, mechanosensors trigger the generation of Ca 2+ signals, which enable cells to maintain the structure of the fibrillar collagen matrix through actomyosin contractile forces. Transient receptor potential vanilloid type 4 (TRPV4) is a mechanosensitive Ca 2+ -permeable channel that, when expressed in cell-matrix adhesions of the plasma membrane, regulates extracellular matrix (ECM) remodeling. In high prevalence disorders such as fibrosis and tumor metastasis, dysregulated matrix rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 185 publications
(305 reference statements)
1
34
0
Order By: Relevance
“…Stepwise deletions revealed that the distal-most part of the Nterminus, more specifically the proline-rich domain, was required for the response to cellular swelling [63]. This finding aligns with the cytoskeletal protein PACSIN3 interacting specifically with this section of the TRPV4 N-terminus [77], which thus may be the point of contact in the proposed interaction between TRPV4 and the cytoskeleton [78][79][80][81] underlying volume-induced activation of TRPV4. The TRPV4 N-terminus may, in addition, modulate the volume sensitivity of the ion channel by binding to the membraneous phosphatidylinositol-4,5-diphosphate, which leads to rearrangements of the tail region and Syndapin3/PACSIN3 [82].…”
Section: Cell Swellingmentioning
confidence: 53%
“…Stepwise deletions revealed that the distal-most part of the Nterminus, more specifically the proline-rich domain, was required for the response to cellular swelling [63]. This finding aligns with the cytoskeletal protein PACSIN3 interacting specifically with this section of the TRPV4 N-terminus [77], which thus may be the point of contact in the proposed interaction between TRPV4 and the cytoskeleton [78][79][80][81] underlying volume-induced activation of TRPV4. The TRPV4 N-terminus may, in addition, modulate the volume sensitivity of the ion channel by binding to the membraneous phosphatidylinositol-4,5-diphosphate, which leads to rearrangements of the tail region and Syndapin3/PACSIN3 [82].…”
Section: Cell Swellingmentioning
confidence: 53%
“…1F and S1C). Mechanical responses are often associated with elevation of cytosolic Ca 2+ signals (16,(22)(23)(24)(25)(26). As such, to measure responses of different midgut cell types, we expressed UAS-GCaMP6s, a genetically encoded Ca 2+ sensor (27), under the control of various drivers, including Myo1A-Gal4 for ECs, Esg-Gal4 for ISCs/EBs, and TrpA1-D-2A-Gal4 for EEs (13,16,18,28,29).…”
Section: Ees Are Activated By Shear Stress Ex Vivomentioning
confidence: 99%
“…Furthermore, these studies revealed the connection of TRPV4 to the stiffness of the matrix, and TRPV4 itself has also been linked to the modulation of the ECM. TRPV4 is responsive to the biophysical changes of the surrounding matrix and can be triggered through signals transmitted through specific ECM polymers [46,47]. Consecutively, it can affect the remodeling of collagen in the ECM, affecting the mechanical features of the matrix [48,49].…”
Section: Trpv-linked Epithelial Mesenchymal Transition and Stiffness Of The Microenvironmentmentioning
confidence: 99%
“…Therefore, deregulation of TRPV and other TRP family channels also plays a major role in the development of several pathophysiological conditions, including various cancers. Mechanosensitive TRPV channels have been linked to cancer progression at least through their ability to both sense and modify mechanically altered microenvironment [45][46][47][48][49], through their association with mechanosensitive Rho GTPases and actin cytoskeleton, leading to altered migratory features [50][51][52][53], as well as due to their role in angiogenesis [54][55][56][57] and cell proliferation [58][59][60]. Many of these channel proteins have also shown potential as therapeutical targets [61,62].…”
Section: Introductionmentioning
confidence: 99%